Beetroot based ORS for treatment of cholera - Atif Amin, Baig; Chandrika, Murugaiah (2019)
Cholera, caused by the bacteria Vibrio cholerae, can be lifethreatening but it is easily prevented and treated. It is caused by eating food or drinking water contaminated with Vibrio cholerae.V. cholerae was first isolated by Italian anatomist Filippo Pacini in 1854. Later Robert Koch publicized the knowledge of cholera. The bacterium’s natural habitat is brackish or saltwater, and globally, cholera cases have increased steadily since 2005. Vaccination and good hygiene are mainstay of cholera prevention. Treatment of cholera consist of oral or intravenous solutions to replace lost fluids. Antibiotics are not part of emergency treatment for mild cases; however, they can reduce the duration of diarrhea by half and also reduce the excretion of the bacteria, thus helping to prevent the spread of the disease.